Investigation of Motivation Levels of National Team Athletes Competing During the COVID-19 Pandemic Crisis (Judo, Wrestling and Taekwondo Example): Descriptive Research. - NAZIROĞLU, Meltem; DEMİRAL, Şengül; ÖZBAR, Nurper (Turkiye Klinikleri Journal of Sports Sciences, 2023)
Objective: The aim of this study is to examine the levels of exercise orientation and motivation in sport among national team athletes in judo, wrestling and taekwondo, who have been away from competition and training for a time during the coronavirus disease-2019 pandemic period. Material and Methods: The study population consisted of a total of 1,472 athletes competing in the sports of judo, wrestling and taekwondo in 2021. To examine the participants' motivation levels, the "Sport Motivation Scale-II", was used. In order to examine the athletes' participation in exercise "Behavioural Regulation in Exercise Questionnaire-2" (BREQ-2), was used. The data were analysed with the SPSS 25 program. Results: According to the research findings, it was determined that judo athletes had higher scores in the "Internal regulation", "Integration" and "Identification" sub-dimensions than wrestling and taekwondo athletes. Wrestling and taekwondo athletes were found to have higher scores than judo players in the BREQ-2. Conclusion: It is important to have knowledge of situations in which athletes are motivated so that they can adapt quickly when they return to sport after being away from training for extraordinary reasons. It is recommended that the relevant subject be dealt with more frequently on elite athletes in terms of the challenging training conditions of combat sports, the rapid adaptation of the athletes to the competitions and the maintenance of their performance.